The Effect of Education on Regional Economic Performance in Canada - Fang, Min (Université d'Ottawa | University of Ottawa, 2008)
Using data collected from the 2001 Canadian Census Profile in E-STAT, the effect of education on regional economic performance is examined at the Canadian census division level. The positive effect of the educational attainment of the census division popu